PENGARUH SOSIAL EKONOMI ORANGTUA TERHADAP HASIL BELAJAR IPS SISWA KELAS VII DAN VIII DI MTs DATUK BATU HAMPAR BAGANSIAPIAPI KABUPATEN ROKAN HILIR - Novi Nuraini; Gimin Gimin; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this study is to find out the effect of social financial of parents to the result of social study of the first dan second year students of MTs Datuk Batu Hampar Bagansiapiapi Rokan Hilir Regency. The population of this research was all the fisrt dan second year students which consist of 53 students, in this research the writer used purposive sampling related to the students who didn’t pass the minimum standart of achievement (KKM). However, only 33 students were participated in this study. The analysis in this research were descriptive, uji normalitas, uji linieritas, uji f, uji t, determinasi and uji persamaan regresi berganda. The result of descriptive analysis show that the majority of education of student’s parentsis <Rp 1.500.000 and beside that, there are nothing of side income from the result of hypothesis test, it was found that there was significant influence between education of parents for the result of students was t value (4,624) > table t (2,042) and sig (0,000) < 0,05and parents financial for the result of student was t value (3,945) > table t (2,042) and sig (0,000) < 0,05. From the result of data analysis, it wa found education value and financial were significant influences for variabel of learning result was t value (18,062) > table f (3,316)and sig (0,000) < 0,05 . Value R square 0,546, that was independence of variabel of influence for depence variabel was 54,6% Where the rest 43,4% was influenced by other variabel that was not consist of this model regresiKey Words: Study of Parents, Income of Parents, Result of Social Study of the First and Second MTs Datuk Batu Hampar Bagansiapiapi